CLIENT’S AND PSYCHOLOGICAL COUNSELORS’ PERSPECTIVE ON THERAPEUTIC ALLIANCE: COMPARISON OF ONLINE, FACE TO FACE, AND PLASEBO GROUPS - Seher Merve ERUS (Fırat University, 2020)
In this research clients and psychological counselors’ therapeutic alliance levels during face to face and online counseling process were examined. 61 individuals (25 clients at face to face group, 21 clients at online group, and 15 participants at placebo group) and six psychological counselors were participated in the study. Psychological counselors offered service to each group. Working Alliance Inventory and Personal Information Form were used as data collection tools. Spearman Brown correlation analysis was used to examine correlations between clients and psychological counselors’ therapeutic alliance levels and Kruskal Wallis test was used to compare therapeutic alliance levels among the groups. As a result of the study there were positive relationships between clients and psychological counselors’ therapeutic alliance (goal, task, and bond factors) at face to face and online group. There was no relationship between participants and psychological counselors’ therapeutic alliance at placebo group. The result of the study revealed no significant differences among face to face and online groups in terms of clients and psychological counselors’ therapeutic alliance. Besides psychological counselors’ therapeutic alliance (goal, task, and bond factors) level in placebo group found significantly lower than face to face and online groups but participants’ goal factors found significantly lower.